2018
DOI: 10.1111/mec.14564
|View full text |Cite
|
Sign up to set email alerts
|

Mitonuclear discordance in wolf spiders: Genomic evidence for species integrity and introgression

Abstract: Systematists and taxonomists have benefited greatly from the emergence of molecular methods. Species identification has become straightforward through DNA barcoding and the rapid build-up of massive DNA barcode reference libraries. In animals, mitonuclear discordance can significantly complicate the process of species identification and delimitation. The causes of mitonuclear discordance are either biological (e.g., introgression, incomplete lineage sorting, horizontal gene transfer androgenesis) or induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 71 publications
2
58
1
Order By: Relevance
“…open Scientific RepoRtS | (2020) 10:1497 | https://doi.org/10.1038/s41598-020-58279-x www.nature.com/scientificreports www.nature.com/scientificreports/ nuclear markers, which in turn can influence the genome in both adaptive and maladaptive ways 5,[19][20][21][22] . Adaptive introgression of mitochondrial DNA may play an important role in speciation and phylogeography 23,24 .While hybridization has been well-documented among pathogenic fungi 21,[25][26][27][28][29][30] , the role of hybridization on the process of speciation of fungal lineages with different life histories and ecological functions is not well understood, including among lichen-forming fungi. The role of gene flow and hybridization in lichen-forming fungal evolution has been a long-standing question [31][32][33][34][35] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…open Scientific RepoRtS | (2020) 10:1497 | https://doi.org/10.1038/s41598-020-58279-x www.nature.com/scientificreports www.nature.com/scientificreports/ nuclear markers, which in turn can influence the genome in both adaptive and maladaptive ways 5,[19][20][21][22] . Adaptive introgression of mitochondrial DNA may play an important role in speciation and phylogeography 23,24 .While hybridization has been well-documented among pathogenic fungi 21,[25][26][27][28][29][30] , the role of hybridization on the process of speciation of fungal lineages with different life histories and ecological functions is not well understood, including among lichen-forming fungi. The role of gene flow and hybridization in lichen-forming fungal evolution has been a long-standing question [31][32][33][34][35] .…”
mentioning
confidence: 99%
“…open Scientific RepoRtS | (2020) 10:1497 | https://doi.org/10.1038/s41598-020-58279-x www.nature.com/scientificreports www.nature.com/scientificreports/ nuclear markers, which in turn can influence the genome in both adaptive and maladaptive ways 5,[19][20][21][22] . Adaptive introgression of mitochondrial DNA may play an important role in speciation and phylogeography 23,24 .…”
mentioning
confidence: 99%
“…Introgression through occasional hybridization needs certainly to be considered in morphologically and ecologically similar congeners that occur in sympatry. Recent genomic studies have shown that it may be more prevalent in spiders than previously assumed (Ivanov, Lee, & Mutanen, ; Leduc‐Robert & Maddison, ). However, we observed no single case of disagreement between morphology and mtDNA (i.e.…”
Section: Discussionmentioning
confidence: 94%
“…Another question related to the mechanisms of genetic exchange in T. cruzi is the mitonuclear discordance observed in some DTUs. This phenomenon can be described as a significant difference in levels of differentiation between nuclear and mitochondrial markers, where nuclear phylogeny is more structured (higher number of and longer branches) than mitochondrial phylogeny (kDNA phylogeny in this case) [37]. In T. cruzi, mito-nuclear discordance is clearly observed in TcIII.…”
Section: Introductionmentioning
confidence: 92%